(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
At the present stage of the development of our Republic, fundamental qualitative changes are determined in all aspects of the life of our society. It is an undeniable fact that the solution to this huge task is carried out in connection with the increase in the mental potential of our citizens. This is closely related to proper education and training. For this, first of all, it is required to bring into order the theoretical foundations of Education. Today, the process of information consumption also assumes a specific culture-it is necessary that such a form of culture becomes a component of human spiritual culture. The culture of information consumption is especially important in the current conditions, when the Internet network is rapidly developing, being one of the characteristic features of globalization processes